Determination of Calcium in Pulses by Complexometric Titration and Overview of Nutritional Parameters (International Journal of Food and Nutritional Sciences, 2022)
Pulses, like cereals, are commonly consumed as a source of protein. They are high in carbohydrates, protein, and dietary fiber, as well as micronutrients. Its importance and use for a range of health conditions have been referenced in ancient writings and the ayurvedic medical system. This paper details a research of calcium measurement in several pulse samples, as well as a discussion of various nutritional aspects. The acid digestion method was used to create sample solutions for the determination of calcium. After that, an aliquot of the sample solution was titrated using the complexometric method by using Disodium salt of Ethylenediamine tetra acetic acid (EDTA). Patton-Reeder's reagent (3-hydroxy-4-[(2-hydroxy-4-sulfonaphthalen-1-yl)diazenyl] naphthalene-2-carboxylic acid) was utilized as an indicator.